El proceso de vinculación con la sociedad y el modelo de evaluación del CACES 2024 en el Instituto Superior Tecnológico Ciudad de Valencia. - Suatunce Vega, Liliana Matilde (2025)
The research work named "The process of community outreach and the CACES 2024 Evaluation Model at Instituto Superior Tecnológico Ciudad de Valencia" focuses on analyzing how the institute has implemented and managed its processes of community outreach within the framework of the CACES Evaluation Model in the year 2024. The research addresses the challenges and opportunities faced by the institution to meet the standards of CACES ( Consejo de Aseguramiento de la Calidad de la Educación Superior) in relation community outreach. The general objective of the thesis was to evaluate the effectiveness of the linkage strategies deployed by the institute with society, in the parameters indicated in the CACES 2024 model. The methodology used was qualitative and documentary, using a descriptive and comparative approach; key institutional documents, such as the Strategic Plan for Institutional Development and evaluation reports, were used to carry out an exhaustive analysis of the planning, execution and fulfillment of community outreach projects. The main results show that, despite the Institute's achievements in outreach, there are still areas that must be improved, such as the coverage of measurable execution in social impact and prospective alignment with the CACES process indicators. The study concludes that it is urgent to strengthen the different aspects of outreach, to follow up on projects and to ensure their future sustainability to meet the proposed levels of quality that will ensure a greater link between the institute and its community and environment